Form Recognition dan Character Mapping Menggunakan Image Segmentation dan Optical Character Recognition - Christian Wibisono; Setia Budi (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
Industry 4.0 revolve the way of thinking in manufacturing factory business. Speed and accuracy become the main focus to survive and To growth. This study aims to build a blue print of an system that will increase both speed and accuracy in form input. This research will use several computer vision technologies like CNN that will used to do form classification and image segmentation, there is also OCR that will take specific information from a document that have been classified with CNN and then transform it into a JSON format which have more generic format and can be used in most common platform.